diseño e implementación de un dispositivo electrónico para la rehabilitación de extremidad inferior en pacientes con pérdida de movilidad parcial - Veintimilla LLivi, Mario Fernando (2023)
The present research project exposes "Design and implementation of an electronic device for the rehabilitation of the lower extremity in patients with partial mobility loss", since the prototype presents characteristics similar to orthoses to align or correct deformities in patients with partial and temporal mobility loss. In the same way, this prototype is low cost that contributes to medical treatment in the form of therapies to recover the natural movement of a lower extremity. Likewise, the prototype is based on scientific documentation based on medical science that entails viable solutions to improve the quality of life being human. It is that new technologies and medicine, when they go together advance at an unimaginable speed, when we refer to the prototype also involve devices and electronic components either digital and analog sensors or development platforms such as Arduino can achieve very acceptable and reliable results with respect to existing devices in the world and especially in countries that develop these devices with a view to prostheses and orthoses more and more Smart who assist in the rehabilitation of patients with temporary injuries